Maximal Chains in Bond Lattices - Ahirwar, Shreya; Fishel, Susanna; Gya, Parikshita; Harris, Pamela; Pham, Nguyen; Vindas Meléndez, Andrés; Vo, Dan Khanh (The Electronic Journal of Combinatorics, 2022)
Let G be a graph with vertex set {1,2,…,n}. Its bond lattice, BL(G), is a sublattice of the set partition lattice. The elements of BL(G) are the set partitions whose blocks induce connected subgraphs of G. In this article, we consider graphs G whose bond lattice consists only of noncrossing partitions. We define a family of graphs, called triangulation graphs, with this property and show that any two produce isomorphic bond lattices. We then look at the enumeration of the maximal chains in the bond lattices of triangulation graphs. Stanley’s map from maximal chains in the noncrossing partition lattice to parking functions was our motivation. We find the restriction of his map to the bond lattice of certain subgraphs of triangulation graphs. Finally, we show the number of maximal chains in the bond lattice of a triangulation graph is the number of ordered cycle decompositions.